THE FLIPPED CLASSROOM: A MODERN APPROACH TO ACTIVE LEARNING (International journal of artificial intelligence, 2025)
The flipped classroom model has emerged as an innovative teaching methodology that challenges traditional instructional approaches. By shifting direct instruction outside the classroom and utilizing class time for interactive learning, this model enhances student engagement, fosters critical thinking, and improves knowledge retention. This article explores the definition, key principles, advantages, challenges, and real-world applications of the flipped classroom method, providing an in-depth analysis of its impact on education.